2015
DOI: 10.1038/modpathol.2015.65
|View full text |Cite
|
Sign up to set email alerts
|

BAP1 (BRCA1-associated protein 1) is a highly specific marker for differentiating mesothelioma from reactive mesothelial proliferations

Abstract: The distinction between malignant mesothelioma and reactive mesothelial proliferation can be challenging both on histology and cytology. Recently, variants of the BRCA1-associated protein 1 (BAP1) gene resulting in nuclear protein loss were reported in hereditary and sporadic mesothelioma. Using immunohistochemistry, we evaluated the utility of BAP1 expression in the differential diagnosis between mesothelioma and other mesothelial proliferations on a large series of biopsies that included 212 mesotheliomas, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
210
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(239 citation statements)
references
References 71 publications
12
210
2
3
Order By: Relevance
“…23 As well, the 100% specificity for BAP1 has been similarly reported in a few studies. 8,23 However, other studies reported lower specificity. For instance, Andrici et al 9 reported 95% specificity (interpreted by them as more likely due to artefactual negative staining), and Walts et al (Table 1), specificity would be 88.6% in our case series (by excluding from the formulae cases with an initial diagnosis uncertain between MM and MH).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…23 As well, the 100% specificity for BAP1 has been similarly reported in a few studies. 8,23 However, other studies reported lower specificity. For instance, Andrici et al 9 reported 95% specificity (interpreted by them as more likely due to artefactual negative staining), and Walts et al (Table 1), specificity would be 88.6% in our case series (by excluding from the formulae cases with an initial diagnosis uncertain between MM and MH).…”
Section: Discussionmentioning
confidence: 90%
“…8,9,[21][22][23][24][25] The aim of this study was to evaluate the utility of BAP1 IHC in the diagnosis of MM in effusions. To do this, we investigated the BAP1 protein expression on a large series of cell blocks from pleural/peritoneal effusions, with a definite diagnosis of MM or an uncertain diagnosis between MM and MH, and benign effusions.…”
mentioning
confidence: 99%
“…Cigognetti and co-workers provided evidence of homozygous deletions in association with heterozygous deletions of the BAP1 locus by FISH analysis in a few cases among their IHC BAP1-negative MM series [40]. Intra-tumor differences in BAP1 LOH were recently reported in sarcomatoid and carcinomatous elements in clear renal cell carcinomas [41].…”
Section: Case D-ii-3) Somatic Mutations In Exonmentioning
confidence: 99%
“…Biallelic inactivation of the tumor suppressor gene BRCA1-associated protein 1 (BAP1) occurs in several cancers (colorectal, renal and malignant mesothelioma). BAP1 deletion on staining and immunohistochemistry is the latest discovery, of special interest to the pathologist, and a very useful marker for a definitive diagnosis of malignant mesothelioma distinguishing it from atypical reactive mesothelial proliferations in effusions [5,6]. Presence of BAP1 deletion increases cancer-specific mortality and risk of recurrence in all cancers, except mesothelioma, where it correlates with a better prognosis [7].…”
Section: Discussionmentioning
confidence: 99%